Antioxidant and Tyrosinase Inhibitory Activities of Flavonoids from Trifolium nigrescens Subsp petrisavi - TOPÇU, GÜLAÇTI; Demirkiran, Ozlem; Sabudak, Temine; Ozturk, Mehmet; Topcu, GÜLAÇTI (My University, 2013)
Trifolium nigrescens was researched for its chemical constituents for the first time. Bioassay-guided isolation of the EtOAc extract from the leaves of T. nigrescens resulted in the purification of a new biflavone, 4-,5,5 -,7,7 --pentahydroxy-3-,3--dimethoxy-3-O-beta-D-glucosyl-3 -,4--O-biflavone (1) along with eleven known compounds consisting of three phenolics (2-4), and eight flavonoid glycosides (5-12). Their structures were determined by extensive ID and 2D NMR, and MS data analyses. The isolated compounds were evaluated for their antioxidant activity and inhibitory activity on mushroom tyrosinase. Highly potent inhibitions Were found by compounds 7 (IC50 = 0.38 mM), 8 (IC50 = 0.19 mM), and 12 (IC50 = 0.26 mM) when compared with standard tyrosinase inhibitors kojic acid (IC50 = 0.67 mM) and L-mimosine (IC50 = 0.64 mM). The antioxidative effect of the isolated compounds and the extracts were determined by using, beta-carotene-linoleic acid, DPPH center dot scavenging, ABTS(+center dot) scavenging, superoxide scavenging, and CUPRAC assays. The experimental findings indicated that all the compounds demonstrated activity in all antioxidant activity tests employed except for the compounds 2-6. Compounds 2-6 showed moderate activity only in ABTS(+center dot) scavenging assay. The new compound 1 exhibited better activity than standard alpha-tocopherol in DPPH center dot scavenging, and ABTS(+center dot) scavenging assays. The results show that T. nigrescens can be regarded as a potential source of antioxidant compounds and tyrosinase inhibitors of significance in both the pharmaceutical and food industries.